Pemberdayaan Guru Di SMP Negeri 2 Kismantoro - Pebriyanti, Ayu Rima; , Prof. Dr. Abdul Ngalim, M.M.,M.Hum; , Dr. Samino, M.M (2015)
The research has three purposes. (1) To describe the teachers performance in SMP Negeri 2 Kismantoro. (2) To describe the headmaster role in the teachers empowerment in SMP Negeri 2 Kismantoro. (3) To describe the problem and solution in teachers empowerment in SMP Negeri 2 Kismantoro. This research is using descriptive qualitative while design of the research is ethnography. Data used is primarily and secondary data. Data sources used is informant, activity and document. Researcher's attendance in this research is as instrument. Data colleting technique used is interview, observation, and document analysis. Data validity is obtained using interactive model data analysis including data collection, data reduction, data presentation and conclusion drawing. Based on the research result in this research it can be three concluded. (1) Teachers performance in SMP Negeri 2 Kismantoro teachers prepare learning tools, implement learning, evaluating learning outcomes. The teachers active in seminary and teachers conference subject (2) Headmaster role in the teachers empowerment in SMP Negeri 2 Kismantoro are increase work spirit, increase professional, increase the effective of teacher workteam. (3) The problem and solution in teachers empowerment in SMP Negeri 2 Kismantoro are school location away from teachers and students domicile. The headmaster do evaluating and monitoring. The headmaster active in founding professional competence.